Combined Endoscopic/Sonographic-based Risk Matrix Model for Predicting One-year Risk of Surgery: A Prospective Observational Study of a Tertiary Centre Severe/Refractory Crohn's Disease Cohort. (8th March 2018) - Rispo, Antonio; Imperatore, Nicola; Testa, Anna; Bucci, Luigi; Luglio, Gaetano; De Palma, Giovanni Domenico; Rea, Matilde; Nardone, Olga Maria; Caporaso, Nicola; Castiglione, Fabiana
Abstract: Background: In the management of Crohn's disease [CD] patients, having a simple score combining clinical, endoscopic, and imaging features to predict the risk of surgery could help to tailor treatment more effectively. Aims: We aimed to prospectively evaluate the 1-year risk factors for surgery in refractory/severe CD and to generate a risk matrix for predicting the probability of surgery at 1 year. Methods: CD patients needing a disease re-assessment at our tertiary inflammatory bowel disease [IBD] centre underwent clinical, laboratory, endoscopic, and bowel sonography [BS] examinations within 1 week. The optimal cut-off values in predicting surgery were identified using receiver operating characteristic [ROC] curves for the Simple Endoscopic Score for CD [SES-CD], bowel wall thickness [BWT] at BS, and small bowel CD extension at BS. Binary logistic regression and Cox regression were then carried out. Finally, the probabilities of surgery were calculated for selected baseline levels of covariates and results were arranged in a prediction matrix. Results: Of 100 CD patients, 30 underwent surgery within 1 year. SES-CD ≥9 (odds ratio [OR] 15.3; p <0.001], BWT ≥7 mm [OR 15.8; p <0.001], small bowel CD extension at BS ≥33 cm [OR 8.23; p <0.001], and stricturing/penetrating behaviour [OR 4.3; p <0.001] were the only independent factors predictive of surgery at 1 year, based on binary logistic and Cox regressions. Our matrix model combined these risk factors, and the probability of surgery ranged from 0.48% to 87.5% [16 combinations]. Conclusions: Our risk matrix combining clinical, endoscopic, and ultrasonographic findings can accurately predict the 1-year risk of surgery in patients with severe/refractory CD requiring a disease re-evaluation. This tool could be of value in clinical practice, serving as the basis for a tailored management of CD patients.